Pengaruh Pengetahuan Wirausaha Dan Dukungam Sosial Terhadap Minat Berwirausaha Siswa SMKS Kabupaten Bogor - Zevender, Poy Saefullah; Mina Mutiah; Mohammad Tanurullah (Jurnal Pendidikan Ekonomi, 2026)
The low level of entrepreneurial intention among Vocational High School (SMK) students poses a significant challenge to the absorption of self-employed labor. Objective: This study aims to analyze the influence of entrepreneurial knowledge and social support on students' entrepreneurial intention. A quantitative approach was employed, utilizing an explanatory survey method with a descriptive-correlational design. The research population comprised 116,483 Private SMK students in Bogor Regency, with a sample of 284 students selected through simple random sampling. Data were analyzed using regression tests to measure both partial and simultaneous effects. Results: The findings indicate that entrepreneurial knowledge has a positive and significant partial effect on entrepreneurial intention (sig. 0.000 < 0.05), contributing 48.5%. Social support also significantly influences intention ($sig. 0.000 < 0.05$), with a contribution of 51.7%. Simultaneously, both variables significantly affect entrepreneurial intention with a coefficient of determination (R2) of 0.619. Entrepreneurial knowledge and social support together account for 61.9% of the variation in students' entrepreneurial intention, while the remaining 38.1% is influenced by factors outside this research model. Based on these findings, schools are encouraged to enhance entrepreneurial literacy not only through theoretical curricula but also through intensive business simulations to deepen students' practical knowledge.